An improved algorithm for channel allocation on direct sequence spread spectrum - Handrizal, M (2011)
Graph coloring is an assignment a color to each vertex, which each vertex that adjacent is given a different color. Graph coloring is a useful algorithm for channel allocation on Direct Sequence Spread Spectrum (DSSS).Through this algorithm,each access point (AP) that adjacent gives different channels based on colors available.Welsh Powell algorithm and Degree of saturation (Dsatur) are the popular algorithms being used for channel allocation in this domain. Welsh Powell algorithm is an algorithm that tries to solve the graph coloring problem.Dsatur algorithm is an algorithm coloring sorted by building sequence of vertices dynamically.However,these algorithms have its weaknesses in terms of the minimum number of channel required.In this study,channel allocation called Vertex Merge Algorithm (VMA) is proposed with aim to minimize number of required channels.It is based on the logical structure of vertex in order to a coloring the graph.Each vertex on the graph arranged based on decreasing number of degree.The vertex in the first place on the set gives a color,and then this vertex is merged with non-adjacent vertex.This process is repeatedly until all vertices colored.The assignment provides a minimum number of channels required.A series of an experiment was carried out by using one computer.Vertex Merge Algorithm (VMA) simulation is developed under Linux platform.It was carried out in Hypertext Preprocessor (PHP) programming integrated with GNU Image Manupulation Program (GIMP) for open and edit image.The experimental results show that the proposed algorithm work successfully in channel allocation on DSSS with the minimum of channels required.The average percentage reduction in the number of required channels among the VMA, Dsatur algorithm and Welsh Powell algorithm in the simple graph is equivalent to 0.0%. Meanwhile between the VMA and Dsatur algorithm in the complex graph is equivalent to 18.1%.However,VMA and Welsh Powell algorithm is not compared in the complex graph since its drawback in terms of not fulfill the graph coloring concept.This is because there are two adjacent vertices have the same color.Overall, even there is no reduction for number of required channel among VMA,Dsatur algorithm and Welsh Powell algorithm in the simple graph,but the outstanding significant contribution of VMA since it has reduction in the complex graph.